2004
DOI: 10.1111/j.1469-8749.2004.tb00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurological recovery in obstetric brachial plexus injuries: an historical cohort study

Abstract: An historical cohort study was conducted to investigate the rate and extent of neurological recovery in obstetric brachial plexus injury (OBPI) and to identify possible prognostic factors in a cohort of children with OBPI from birth to 7 years. All children (n=56; 31 females, 25 males) with OBPI were evaluated at fixed time intervals by one examiner. They underwent a final neurological examination at a mean age of 3 years 10 months (range 1 to 7 years). Neurological outcome was not as favourable as is often re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(108 citation statements)
references
References 15 publications
3
99
0
6
Order By: Relevance
“…The AMS score alone is not enough to evaluate recovery outcomes in the toddler and child but does work very well as early evidence of recovery in the young infant. In keeping with Hoeksma et al, 14 Bisinella and Birch, 3 and Waters, 21 our GZ guideline also places strong emphasis on the assessment of shoulder function. These authors have made a strong case that if recovery of shoulder as well as biceps function is not present by 1 month of age then there is a significant risk of incomplete recovery.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The AMS score alone is not enough to evaluate recovery outcomes in the toddler and child but does work very well as early evidence of recovery in the young infant. In keeping with Hoeksma et al, 14 Bisinella and Birch, 3 and Waters, 21 our GZ guideline also places strong emphasis on the assessment of shoulder function. These authors have made a strong case that if recovery of shoulder as well as biceps function is not present by 1 month of age then there is a significant risk of incomplete recovery.…”
Section: Discussionsupporting
confidence: 55%
“…Other groups have also demonstrated similar findings. 14,19,21 It is imperative that families be informed that incomplete recovery by 5-6 months equates with incomplete recovery in the future. The GZ ends at 6 months, suggesting that the decision for surgery should be clear by then.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some conflicting reports [2,17,21], probably more than 70% of all infants presenting with OBPP will have a very good spontaneous recovery. The remaining patients are destined for poor functional outcomes and they are potential candidates for nerve surgery.…”
Section: Introductionmentioning
confidence: 94%
“…Although full recovery has been reported in up to 92% of cases 6 , recent studies have reported more modest recovery rates of 66% to 80% 7,8 . Children whose neurological deficit does not resolve may experience softtissue contractures and osseous deformities that can significantly impair upper-extremity function and appearance [9][10][11][12] .…”
mentioning
confidence: 99%